Public Service Intervention in Coffee Plantations Optimisation of Rejang Lebong District - Anzori, Anzori; Susena, Karona Cahya (Jurnal Manajemen Pelayanan Publik, 2025)
Rejang Lebong Regency is one of the main coffee-producing regions in Indonesia, with great potential to increase coffee productivity and added value. However, coffee management in this area still faces various challenges, such as low production efficiency, lack of application of modern technology, and hesitant market access and policy support. This study purposed to determine the causes of the low income and welfare of coffee farmers in Rejang Lebong Regency and as a promotion and branding of coffee in Rejang Lebong Regency that has not been recognized at the national and international levels. The method used included descriptive research, which explained factual phenomena conceptually, with data collection through surveys. The results showed that greater efforts or strengths are still required to overcome various kinds of weaknesses and utilize existing opportunities to overcome obstacles. The research recommended the integration of community-based coffee development programs and policy support from the local government to create a sustainable coffee management system. Optimizing coffee management in Rejang Lebong Regency is expected to encourage the improvement of farmers' welfare, environmental sustainability, and the strengthening of the regional economy.